The Positioning of Coffee Shops Based on Consumer Perceptions: Study of Coffee Shops in Brebes Regency - Aziz, Muhamad Syahrul; Iskandar, Khalid; Ikhwan, Syariefful (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The coffee shops are starting to bloom in Indonesia and are attracting more and more coffee lovers. Coffee shop growth rates also occur in Brebes Regency. Many new coffee shop brands offer new facilities and concepts to the community, especially the Brebes Regency area, so that every coffee shop entrepreneur must know the positioning in order to survive in the competition. The purpose of this study was to determine the mapping of consumer perceptions of the 3 coffee shops included in the research object in Brebes Regency, namely Kelirumology Coffee, Rajaswa Coffee and Warkop 12 based on the attributes of service quality, brand, location, facilities, price, menu diversity, and atmosphere so that useful to know the positioning of the coffee shop. Positioning is determined by reading the perceptual maps generated based on multidimensional scaling (MDS) analysis. The research data were obtained from questionnaires, library research, and direct observation according to the research objectives. The analysis technique uses multidimensional scaling with a sample of 86 respondents from consumers who have visited the 3 coffee shops. The results showed that consumers have their own perception of each brand based on the attributes of service quality, brand, location, facilities, price, menu variety and atmosphere. On the perception map, the coffee shop brand Kelirumologi Kopi leads because it is in quadrant I with positive coordinates in each dimension. Coffee shop brand Warkop 12 is in quadrant III. The Rajaswa Coffee brand is in quadrant IV. The results of the Kelirumologi Coffee coffee shop mapping lead with superior menu diversity, prices and facilities. But Kelirumologi Kopi has a weakness in brand attributes. Rajaswa Coffee coffee shop ranks second with excellence in brand and location attributes. But Rajaswa Coffee has weaknesses in the attributes of service quality and menu variety. Coffee shop Warkop 12 last place with excellence in service quality and atmosphere. And Warkop 12 has weaknesses in the attributes of location and price.